The Roles of Tax Morale, Tax Fairness, and Tax Simplicity in Enhancing Tax Compliance Behavior Through Tax Compliance Intention at The Jember Tax Office - Deddy Dwi; Qomariah, Nurul; Nyoman Putu Martini, Ni (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Taxes play a very important role in financing various public needs. Enhancing tax compliance is crucial to increasing tax revenues. This study aims to investigate the impact of tax morality, tax fairness, and tax simplicity on tax compliance behavior through tax compliance intentions at the Jember Tax Office. The sample used was 400 respondents. This study uses the Structural Equation Modelling (SEM) model. The results show that tax moral, tax fairness, tax simplicity, and tax compliance intention have a direct and significant effect on tax compliance behavior, respectively. A similar phenomenon also occurs in the connections between tax morals, tax fairness, and tax simplicity with tax compliance intention. Tax compliance intention acts as a mediator of the relationship between tax fairness and tax compliance behavior. On the other hand, tax compliance intention cannot mediate the correlation between tax morality and tax compliance behavior as well as the relationship between tax simplicity and tax compliance behavior.